2007
DOI: 10.1194/jlr.m700051-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid is a potent inhibitor of fatty acid and cholesterol synthesis in C6 glioma cells

Abstract: Glial cells play a pivotal role in brain fatty acid metabolism and membrane biogenesis. However, the potential regulation of lipogenesis and cholesterologenesis by fatty acids in glial cells has been barely investigated. Here, we show that physiologically relevant concentrations of various saturated, monounsaturated, and polyunsaturated fatty acids significantly reduce [1-14 C]acetate incorporation into fatty acids and cholesterol in C6 cells. Oleic acid was the most effective at depressing lipogenesis and cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
76
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 48 publications
(76 reference statements)
14
76
0
Order By: Relevance
“…A recent report showed that oleic acid strongly reduced acetyl-CoA carboxylase activity and was an inhibitor of fatty acid synthesis in C6 glioma cells. 22 Interestingly, compound 1 is a glycoside of oleyl alcohol, and the presence of the oleyl group was the main structural difference with respect to the parent glycosides that resulted less inhibitory of glioma cell division than 1. 7 The treatment of C6 cells with oleic acid (100 µM) for 24 h afforded a 1 H NMR spectrum similar to that obtained with 1 (10 µM) (Figure 1c), in which the major metabolic change was also the intensity of the signal at 0.67 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report showed that oleic acid strongly reduced acetyl-CoA carboxylase activity and was an inhibitor of fatty acid synthesis in C6 glioma cells. 22 Interestingly, compound 1 is a glycoside of oleyl alcohol, and the presence of the oleyl group was the main structural difference with respect to the parent glycosides that resulted less inhibitory of glioma cell division than 1. 7 The treatment of C6 cells with oleic acid (100 µM) for 24 h afforded a 1 H NMR spectrum similar to that obtained with 1 (10 µM) (Figure 1c), in which the major metabolic change was also the intensity of the signal at 0.67 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…After incubated for 48 h, cells were treated with LY294002 (0, 10, 20, 30, 40, 50 μmol/l), rapamycin (1, 10, 30, 50, 90 nmol/l) and NVP-BEZ235 (0.1, 1, 10, 500, 1000, 2000 nmol/l). The viability was examined at incubation for 6, 12, 24, 36 h according to the process by Natali (Natali et al, 2007). Cell monolayers were incubated for 4 h with 1 mg/ml MTT (Beyotime, Jiangsu, China), which is converted from the yellow tetrazolium compound to the purple formazan derivative by mitochondria of living cells.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Consumption of enough alcohol to achieve breath alcohol levels of even 50 mg% is sufficient for plasma acetate levels to approach 1-2 mM, beyond which the plasma acetate concentration does not rise (6,9,10,12,13). Acetate travels to other organs, including the brain, for use as an energy substrate (14) and in fatty acid and cholesterol biosynthesis (15,16). The conversion of ethanol to acetate begins with metabolism to acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%